The directionality of uncertainty expressions and the foreign language effect - Zhang, Yuqian; De Zoysa, Anura; Cortese, Corinne (2020)
Purpose – This study investigates two issues inherent in accounting judgements: (1) the directional influence of uncertainty expressions and how they might positively or negatively affect accounting judgements and (2) the foreign-language effect (FLE), which refers to the reduction of judgement bias that occurs when an accounting judgement is made in one’s foreign language. This study examines both issues in the context of accounting judgements made in Chinese and English languages.